PENGEMBANGAN LEMBAR KERJA PRAKTIKUM MATA PELAJARAN INSTALASI MOTOR LISTRIK KELAS XITEKNIK INSTALASI TENAGA LISTRIK DI SMK NEGERI 1 LUBUK PAKAM - Erwin Yusuf Nasution; Muhammad Amin (Universitas Negeri Medan, 2022)
AbstractThis study aims to develop a practicum worksheet for class XI TITL electric motor installation subjects at SMKN 1 Lubuk Pakam, to test the feasibility of the practicum worksheet for electric motor installation subjects that have been made for class XI at SMKN 1 Lubuk Pakam. The methodology of this research is research and development (Research & Development) with the development model of Four-D Models. Four-D Models consists of 4 stages, namely: define, design, develop, disseminate. The Dissaminate stage was not carried out due to the narrow scope of research. The questionnaire is validated by an evaluation expert. Based on the results of the analysis and discussion, it is known that this development research produces learning resources in accordance with the syllabus, namely practicum worksheets consisting of 11 practical activities, the feasibility level of practicum worksheets is known from the results of the assessment of material experts, media experts, and the results of teacher and student responses. Abstract must reflect the overall substance of the article content and be able to help readers determine its relevance to their interests and decide whether to read the document in its entirety. The results of material expert validation covering aspects of content feasibility, language, presentation, and benefits reached an average score of 116 with a percentage of 92.8% in the